2013
DOI: 10.1093/rheumatology/ket375
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 endogenous ligand MRP8/14 level in enthesitis-related arthritis and its association with disease activity and TLR4 expression

Abstract: MRP8/14 levels are increased in the plasma of ERA patients and are higher in those with active disease and the levels decrease in patients who respond to treatment, suggesting that it may be a good biomarker during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Hammer et al 18 showed a strong correlation between plasma levels of calprotectin and joint damage in patients with rheumatoid arthritis. Rahman et al 22 reported elevated plasma levels of calprotectin in patients with enthesitis-related arthritis. They suggested that patients with an active disease had higher plasma levels of calprotectin compared with those of control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Hammer et al 18 showed a strong correlation between plasma levels of calprotectin and joint damage in patients with rheumatoid arthritis. Rahman et al 22 reported elevated plasma levels of calprotectin in patients with enthesitis-related arthritis. They suggested that patients with an active disease had higher plasma levels of calprotectin compared with those of control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that endogenous ligands induce proinflammatory response from monocytes in patients and it has been reported that both MRP8/14 and TNC levels are elevated in patients with ERA and AS (12,13,18,21). We studied the production of these ligands on stimulation of monocytes and found that indeed, patients cells produced higher levels of TNC & MRP8/14 as compared to HC.…”
Section: Discussionmentioning
confidence: 91%
“…ERA patients also show gut dysbiosis and presence of autoantibodies associated with inflammation of gastrointestinal mucosa like antibodies to tissue transglutaminase or anti-Saccharomyces cerevisiae antibodies (17). They have elevated fecal calprotectin, high pro-inflammatory cytokines (TNF and IL-6) in synovial fluid (SF) and TLR4 endogenous ligands (TNC and MRP8/14) in serum (18)(19)(20)(21)(22). In addition, they also have increased TLR2 and 4 expression on monocytes in blood and SF (8).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, others have reported increased concentrations of endogenous ligand MRP18/4 in plasma and reduced TLR4 expression (Rahman et al. 2014). The fact we detected soluble forms of TLR2 and TLR4, with the latter being differentially regulated, is further evidence of the importance of TLR4 in inflammatory components/mechanisms associated with OA, which shape the OA disease concept (Houard et al.…”
Section: Discussionmentioning
confidence: 99%